Perioperative Outcomes of Different Surgical Methods Among Bladder Cancer Patients Undergoing Radical Cystectomy With Neobladder Urinary Diversion - 김학주; 예창희(Ye Changhee); 김진혁(Kim Jin Hyuck); 김환익(Kim Hwanik); 이상철; 변석수; 오종진 (Daehan bi'nyogi jong'yang haghoeji/The Korean journal of urological oncology, 2021)
Purpose: To compare perioperative outcomes according to surgical methods among bladder cancer patients who underwent radical cystectomy (RC) with neobladder urinary diversion.Materials and Methods: Between June 2007 and January 2020, 89 bladder cancer patients who received RC with neobladder urinary diversion were enrolled in this study. Patients were stratified into surgical methods – (1) open RC with neobladder (ONB) reconstruction, (2) robotassisted RC (RARC) with extracorporeal neobladder (ECNB) reconstruction, and (3) RARC with intracorporeal neobladder (ICNB) reconstruction. Perioperative outcomes were compared among the 3 groups, with major complications defined according to Clavien-Dindo grades III–V within 90 days. Logistic regression analysis was performed to identify significant factors for postoperative complications.Results: Of 89 patients, 28 (31%) had ONB, 31 (35%) had ECNB, and 30 (34%) had ICNB. The median operative time was 471 minutes, and the ICNB group (424.5 minutes) was significantly less than ONB (444.5 minutes) and ECNB groups (542.9 minutes) (p=0.001). Transfusion rate was also significantly less in the ICNB group (13%) (p=0.001). Complications were recorded in 67 patients (75%) and major complications in 22 of all patients (25%). The major complication rate was significantly less in ICNB (13.4%) than in ONB (25%) and ECNB (35%) (p=0.003). Multivariate analysis showed surgical methods (ICNB) (odds ratio [OR], 0.709; p=0.003) and age (OR, 1.150; p=0.001) were significant factors related to occurrence of major postoperative complications.Conclusions: RARC with ICNB reduces postoperative complications compared to ONB and ECNB. KCI Citation Count: 0